2011
DOI: 10.2140/agt.2011.11.2941
|View full text |Cite
|
Sign up to set email alerts
|

Representation spaces of pretzel knots

Abstract: We study the representation spaces $R(K;\bf{i})$ as appearing in Kronheimer and Mrowka's framed instanton knot Floer homology, for a class of pretzel knots. In particular, for pretzel knots $P(p,q,r)$ with $p, q, r$ pairwise coprime, these appear to be non-degenerate and comprise representations in SU(2) that are not binary dihedral.Comment: 30 pages, 3 figures. This is the published version. It is more general than the previous version regarding the values $p,q,r$. Furthermore, rewritten according after r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…The space R(S 3 , K) for K any pretzel knot is identified by Raphael Zentner in [21]. We sketch what happens when one decomposes a pretzel knot along a Conway sphere, to obtain two tangles.…”
Section: Tangles In Pretzel Knot Complementsmentioning
confidence: 99%
“…The space R(S 3 , K) for K any pretzel knot is identified by Raphael Zentner in [21]. We sketch what happens when one decomposes a pretzel knot along a Conway sphere, to obtain two tangles.…”
Section: Tangles In Pretzel Knot Complementsmentioning
confidence: 99%
“…It is conjectured that there is similar spectral sequence in that context.) Zentner [37] showed that for some alternating pretzel knots there are non-binary dihedral traceless representations (in contrast to 2-bridge knots), so that for these families one expects there to be non-trivial differentials in the singular instanton chain complex.…”
Section: Introductionmentioning
confidence: 99%
“…We list a few cases explicitly. The claims on the representation spaces of pretzel knots can be found in [3] and [19].…”
Section: 5mentioning
confidence: 99%
“…• For the pretzel knot P (−3, 5, 7) we have rk(Khr(P (−3, 5, 7))) = 15, whereas R(P (−3, 5, 7); i) contains the conjugacy class of the reducible and 16 conjugacy classes of irreducible non binary dihedral representations (see the table of the example in [19] where 3 errors occur that yield a total error of 1 which multiplied by two gave the wrong claim of 18 conjugacy classes).…”
Section: 5mentioning
confidence: 99%